Virtual Learning Environment in the training of teachers in scientific research - Claudia Carolina Lacruhy Enríquez; Arturo González Torres; María Luisa Pereira Hernández (Universidad de Guadalajara, 2024)
The objective of this research was to evaluate the Scientific Research Project Design Workshop (TDPIC), aimed at the teaching staff of the Tecnológico Nacional de México (TECNM), and focused on the Research Design Canvas model for the design of research projects. This case study is intrinsic, with a quantitative methodology of descriptive and explanatory scope. The workshop was conducted with an instructional design following the ADDIE model in a virtual learning environment (VLE), and considered a sample of 17 teachers who attended the workshop, belonging to five TECNM technology centres. At the end of the workshop, a survey was applied to the participants in order to measure their satisfaction with the digital resources used, the achievement of significant learning and the understanding of the method explained; this evaluation was positive, as the teachers indicated a high degree of satisfaction in the different dimensions of the workshop. It is concluded that the TDPIC was relevant and favoured the training process of the participating teachers.